Aplikasi teknik Peppers Ghost dalam diorama panggung Mak Yong Kelantan - Ahmad Alif Ashraf Mohd Rozali (Tanjong Malim, 2023)
Aplikasi teknik Peppers Ghost dalam diorama panggung Mak Yong Kelantan by Ahmad Alif Ashraf Mohd Rozali